Danish translation and cultural adaption of the Person-Centred Practice Inventory-Staff and Person-Centred Practice Inventory-Care questionnaires - Elizabeth Rosted; Elizabeth Rosted; Mette Kjerholt; Bibi Hølge-Hazelton; Tanya McCance; Brendan McCormack; Thora Thomsen (Frontiers in Health Services, 2025)
BackgroundInternationally, person-centred practice is a recognized standard of quality care influencing the experience of care for healthcare professionals, service users, families and care partners. To measure the experience from the perspectives of both caregivers and patients, the instruments Person-Centred Practice Inventory-Staff (PCPI-S) and the Person-Centred Practice Inventory-Care (PCPI-C) have been developed, which are both theoretically aligned with McCormack and McCance's person-centred framework. In this paper, we present translation and cultural adaption of the questionnaires into Danish.MethodsA model including translation and cultural adaption of both the PCPI-S and the PCPI-C questionnaires was used. The translation and cultural adaption took place from September 2021 to March 2022 and was conducted within the context of a Danish University Hospital.ResultsSix steps were included in the translation and cultural adaption. Discrepancies were addressed and revised by the expert committee until a consensus was reached on a reconciled version.ConclusionAs person-centred practice is a recognized standard of quality influencing the experience of care for healthcare professionals, service users, families and care partners, it has been important to translate the questionnaires PCPI-S, a measure of staff's perception of person-centred practice, and PCPI-C, a measure of patients’ perception of person-centred practice into Danish. Based on this, we now have a Danish instrument that may give the patients a voice by examining to what extent they experience person-centred care in our hospital. This will hopefully support learning and further development of a person-centred culture.